Isolation of bacteria from bovine meat obtained from backyard slaughter in Kelantan - Mohd Azam Khan Goriman Khan; Imad Ibrahim Ali Al-Sultan; Fazlina,F.; Jasbir.S (2011)
The objective of this study is to determine the degree of superficial bacterial contamination in superficial and deeper layers of raw bovine meat sold to customers at backyard meat stalls and open wet markets. A total of 150 meat samples were obtained from various meat stall and wet market in Kota Bharu, Kelantan. The meat surface were scrapped and cut to a deeper layer (2cm deep) to screen the bacteria. The total plate count (TPC) was taken. Several potential pathogenic bacteria were found mainly on the surface of the meat. The deeper layers of the meat showed less bacterial contamination especially in the next morning. The TPC also showed that the surface bacteria in the morning or afternoon was significantly (P < 0.05) higher than the deeper layers of the meat. The results reflect the poor conditions in slaughtering and handling of cattle carcasses, as well as hygiene deficiencies within the area of Kota Bharu. The high prevalence of potential pathogenic bacteria represents a real danger and is a threat to public health